FEMINISM IS FOR ANGRY WHITE WOMEN: EXPLORING IMAGES OF FEMINISM ON REDDIT.COM - Bergstrom, Kelly (AoIR Selected Papers of Internet Research, 2015)
Feminism is a movement with a reasonable goal: the economic, political, and social equality of the sexes. Third wave feminists will frequently speak of “feminisms” that makes room for a multitude of theoretical underpinnings, motivations, and action plans, and yet this plurality is something that often gets lost in discussions outside of explicitly feminist spaces. To explore how feminism is portrayed in everyday contexts I present a case study about the use of “image macros” on Reddit.com (a popular news aggregate website) to discuss feminism.